2006
DOI: 10.1093/molbev/msl108
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Terminal Regions of the Streptomyces Linear Chromosome

Abstract: Comparative analysis of the Streptomyces chromosome sequences, between Streptomyces coelicolor, Streptomyces avermitilis, and Streptomyces ambofaciens ATCC23877 (whose partial sequence is released in this study), revealed a highly compartmentalized genetic organization of their genome. Indeed, despite the presence of specific genomic islands, the central part of the chromosome appears highly syntenic. In contrast, the chromosome of each species exhibits large species-specific terminal regions (from 753 to 1,39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 53 publications
8
97
1
Order By: Relevance
“…Interestingly, AICESco5349 flanks the whiE cluster (Bentley et al, 2002) encoding the enzymes to synthesise the grey polyketide spore pigment (Davis and Chater, 1990) and AICESco3250 flanks the calcium-dependent antibiotic (CDA) biosynthetic gene cluster. The two AICEs are absent on the highly syntenic core region of the S. lividans genome (Jayapal et al, 2007) and the S. ambofaciens genome lacks the CDA cluster and also the complete region containing the whiE cluster and AICESco5349 (Choulet et al, 2006). Possibly, these AICEs are associated with the acquisition of these secondary metabolite clusters in S. coelicolor.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, AICESco5349 flanks the whiE cluster (Bentley et al, 2002) encoding the enzymes to synthesise the grey polyketide spore pigment (Davis and Chater, 1990) and AICESco3250 flanks the calcium-dependent antibiotic (CDA) biosynthetic gene cluster. The two AICEs are absent on the highly syntenic core region of the S. lividans genome (Jayapal et al, 2007) and the S. ambofaciens genome lacks the CDA cluster and also the complete region containing the whiE cluster and AICESco5349 (Choulet et al, 2006). Possibly, these AICEs are associated with the acquisition of these secondary metabolite clusters in S. coelicolor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that telomeric regions in S. ambofaciens are frequently deleted by induction of mutagenesis (38). Analysis revealed that monoterpene cyclase (SAML0357) and methyltransferase (SAML0358) genes were located near the left telomere.…”
Section: Production Of Volatile Terpenoid Metabolites In Actinomycetementioning
confidence: 99%
“…AM287205). Moreover, as the synteny is strong in the central region of the S. coelicolor and S. ambofaciens (Choulet et al, 2006), the other des genes are likely to be conserved as well and present in the same chromosomal region. Analysis and annotation of the chromosome arm sequences identified a cluster in the right arm virtually identical (80-94 % identity at the protein level) to the cch cluster found in S. coelicolor (coding sequences SAMR0548 to SAMR0559, accession no.…”
Section: Conservation Of the Cch And Des Clusters In S Ambofaciensmentioning
confidence: 99%
“…The sequence of about 1?4 Mb of each chromosome arm of S. ambofaciens ATCC 23877 has been determined (Choulet et al, 2006). In addition, the insert extremities of about 5000 clones from a BAC library of the S. ambofaciens chromosome have been sequenced, leading to 40 % coverage of the complete chromosome and providing some information on the genes present in the central part of the chromosome.…”
Section: Conservation Of the Cch And Des Clusters In S Ambofaciensmentioning
confidence: 99%